Historical Analysis of Women’s Inheritance Rights in East Africa (Kenya, Uganda, and Tanzania) and the Influence of Colonialism - Kodiyo, Kenneth Kaunda (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2023)
The article examines the growth of inheritance laws in the former British colonized East African countries Kenya, Uganda, and Tanzania. It discusses how colonial rule changed the traditional system of inheritance and imposed its laws, leading to confusion and leaving women unprotected. The article highlights the need for reforms in the law of succession and the implementation of statutory laws that protect widows and children. The current laws in Kenya, including the Inheritance Act and Matrimonial Property Act, offer protection to women, but the laws in Uganda and Tanzania need to be reviewed to ensure equal treatment of all family members in case of intestate succession. Finally, the article overviews inheritance laws in the three East African countries.